2016
DOI: 10.1590/1516-4446-2015-1801
|View full text |Cite
|
Sign up to set email alerts
|

Serum BDNF levels in unaffected first-degree relatives of patients with bipolar disorder

Abstract: Objective: Unaffected relatives of bipolar disorder (BD) patients have been investigated for the identification of endophenotypes in an attempt to further elucidate the pathophysiology of the disease. Brain-derived neurotrophic factor (BDNF) is considered to be implicated in the pathophysiology of BD, but its role as an endophenotype has been poorly studied. We investigated abnormal serum BDNF levels in BD patients, in their unaffected relatives, and in healthy controls. Methods: BDNF levels were obtained from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 31 publications
0
9
0
Order By: Relevance
“…Serum BDNF levels were found to be decreased [91] or unchanged [92, 93] in BD-P and BD-FDR compared to healthy controls. Duffy et al reported that the BDNF genotype significantly moderates the association between high-risk status for both gene expression and protein levels in BD offspring [88].…”
Section: Resultsmentioning
confidence: 99%
“…Serum BDNF levels were found to be decreased [91] or unchanged [92, 93] in BD-P and BD-FDR compared to healthy controls. Duffy et al reported that the BDNF genotype significantly moderates the association between high-risk status for both gene expression and protein levels in BD offspring [88].…”
Section: Resultsmentioning
confidence: 99%
“…This process involves dysfunctions in several systems, potentially affecting cellular resilience and neural plasticity (Berk et al, 2011;Grande et al, 2016;Vavakova et al, 2015). This vulnerability seems to be related to increased inflammation, where cytokines seem to play a role, as well as a number of modifications caused by increased oxidative stress, mitochondrial dysfunction and a decrease in neurotropic factors (Cunha et al, 2006;Fernandes et al, 2011;Gigante et al, 2011;Kapczinski et al, 2010;Kapczinski et al, 2008;Nery et al, 2016). The concept of neuroprogression in BD also reflects neurodegeneration in these patients.…”
Section: Neuroprogression In Bipolar Disordermentioning
confidence: 99%
“…The study by Nery et al 2 recently published in Revista Brasileira de Psiquiatria was the first to examine peripheral brain-derived neurotrophic factor (BDNF) levels in unaffected siblings of patients with BD. Their ultimate goal was to investigate whether abnormal expression of this neurotrophin might represent an endophenotype of illness, i.e., a quantitative trait that is intermediate between the disease phenotype and its underlying biological process.…”
Section: Referencesmentioning
confidence: 99%
“…2 This places the regulation of immune responses as an important target in the pathophysiology of schizophrenia and BD. In this context, it should be noted that melatonin plays an important role in the regulation of both immune and glial cell reactivity, including through its autocrine effects, which worldleading work by Markus et al in Brazil has shown.…”
mentioning
confidence: 99%
See 1 more Smart Citation